2001
DOI: 10.1002/1097-0215(200002)9999:9999<::aid-ijc1075>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced antitumor efficacy of doxorubicin when given as the prodrug DOX-GA3 in combination with a monoclonal antibody ?-glucuronidase conjugate

Abstract: A glucuronide doxorubicin prodrug N‐[4‐doxorubicin‐N‐carbonyl (oxymethyl) phenyl] O‐β‐glucuronyl carbamate (DOX‐GA3) has been developed to improve the antitumor effects of doxorubicin (DOX). The prodrug was originally designed to be activated into drug by human β‐glucuronidase (GUS) released from tumor cells in necrotic areas of tumor lesions. The aim of this study was to further improve the antitumor effects of DOX‐GA3 by means of antibody‐directed enzyme prodrug therapy (ADEPT). We thus investigated if the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 22 publications
1
33
1
Order By: Relevance
“…All showed much higher in vitro cytotoxic activity than edrecolomab, but the two high-affinity antibodies ING-1 and 3622W94 turned out to be much less tolerable than edrecolomab due to induction of acute pancreatitis. Conjugation of the Ep-CAM-specific murine monoclonal antibody 323/A3 human with beta-glucuronidase is a prodrug approach designed to locally augment the anti-tumour effect of doxorubicin (Houba et al, 2001). A fusion protein between a single-chain antibody and a bacterial toxin is currently being tested for local treatment of head and neck tumours in a phase I trial (Quenneville et al, 2005), and has shown extraordinary antitumour activity and potency in a xenograft model (Di Paolo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…All showed much higher in vitro cytotoxic activity than edrecolomab, but the two high-affinity antibodies ING-1 and 3622W94 turned out to be much less tolerable than edrecolomab due to induction of acute pancreatitis. Conjugation of the Ep-CAM-specific murine monoclonal antibody 323/A3 human with beta-glucuronidase is a prodrug approach designed to locally augment the anti-tumour effect of doxorubicin (Houba et al, 2001). A fusion protein between a single-chain antibody and a bacterial toxin is currently being tested for local treatment of head and neck tumours in a phase I trial (Quenneville et al, 2005), and has shown extraordinary antitumour activity and potency in a xenograft model (Di Paolo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the doxorubicin concentration in the heart (target organ for dose-limiting toxicity) were up to 5-fold lower after administration of DOX-GA3 compared with doxorubicin exposure alone (Houba et al, 2001a). It should be realized, however, that glucuronidated prodrugs are not activated in small non-necrotic tumors due to low levels of ␤-glucuronidase (Houba et al, 2001b). Therefore, the therapeutic potential of these prodrugs seems limited.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…An almost 5-fold higher doxorubicin peak concentration in the tumor was observed after DOX-GA3 administration to mice compared with doxorubicin administration, whereas the doxorubicin concentration in the heart (target organ for doselimiting toxicity) were up to 5-fold lower after administration of DOX-GA3 compared with doxorubicin (Houba et al, 2001a). An ADEPT approach with an enzyme immunoconjugate prepared from ␤-glucuronidase and a carcinoma-specific monoclonal antibody showed improved antitumor activity in mice compared with DOX-GA3 administration alone (Houba et al, 2001b). Two ␤-glucuronyl carbamate-based prodrugs of paclitaxel (paclitaxel glucuronide) were synthesized and a DNA intercalation, inhibition of topoisomerase II, and redox cycling (oxidative stress).…”
mentioning
confidence: 99%
“…4A, DOX-propGA3 is firstly hydrolyzed and released from the core of the micelles or from (free) polymer chains as an intermediate prodrug of DOX, DOX-GA3. This compound is a substrate for β-glucuronidase, which converts it into free DOX after cleavage of the glucuronide spacer 44 . Consequently, in the absence of enzyme, only DOX-GA3 is progressively released from the micelles (as detected by HPLC; Fig.…”
Section: Resultsmentioning
confidence: 99%